Malrotation of Gut with Internal Mesocolic Hernia Mimicking Mesenteric Cyst - Jafor, Md MA; Uddin Ahmed, SM Safir; Islam, Md Anwarul; Siddiqui, AB; Bari, Md Iqbal (TAJ: Journal of Teachers Association, 2011)
Various clinical presentations from chronic abdominal pain to acute midgut volvulus with ischaemic bowel injury may result from failure of normal intestinal rotation and fixation. A patient having malrotation and internal herniation of gut clinically presented to us with intermittent abdominal pain, bilious vomiting and abdominal mass mimicking mesenteric cyst. This is a very rare and exceptional form of presentation of malrotation of gut. Rarity of the clinical presentation leads us to report this case. DOI: http://dx.doi.org/10.3329/taj.v14i2.8395 TAJ 2001; 14(2): 90-91